Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

GM2/GM3 controls the organizational status of CD82/Met microdomains: further studies in GM2/GM3 complexation - Ronan C. M. Santos; Daniela M. S. Lucena; Hector F. B. R. Loponte; Frederico Alisson-Silva; Wagner B. Dias; Roberto D. Lins; Adriane R. Todeschini (Glycoconjugate Journal, 2022)

Treatment of aqueous wastes by means of Thermophilic Aerobic Membrane Reactor (TAMR) and nanofiltration (NF): process auditing of a full-scale plant - M. C. Collivignarelli; A. Abbà; A. Frattarola; S. Manenti; S. Todeschini; G. Bertanza; R. Pedrazzani (Environmental Monitoring and Assessment, 2019)

Evaluation of soil toxicity using different biotests on Pisum sativum : a case study - N. Massa; P. Cesaro; V. Todeschini; E. Bona; S. Cantamessa; G. Berta (Plant Biosystems, 2018)

Trends in long daily rainfall series of Lombardia (northern Italy) affecting urban stormwater control - S. Todeschini (International Journal of Climatology, 2012)
Analyses of six daily rainfall series (Milano, Bergamo, Brescia, Como, Mantova, and Sondrio) are used to assess trends in yearly precipitation behaviour (precipitation height and number of wet days; precipitation height and number of wet days for different classes of daily precipitation; precipitation height related to one wet day; number of dry days between wet days) over Lombardia, northern Italy. The time series analysis was performed with two non‐parametric rank based tests: the Mann Kendall test and Sen's estimator of slope. Also a new and advantageous procedure that combines a time series model and Bayesian statistics through the Markov Chain Monte Carlo (MCMC) method of Gibbs sampling is adopted to model trends. Globally, the different methods detect the same tendencies. The results point toward a significant decreasing trend in the annual number of wet days and an increasing tendency in the mean and maximum precipitation height related to one day, with a generalized increasing tendency for the number of dry days between wet days. These trends affect the rainfall runoff process and the pollutant dynamics on urban areas and in drainage systems and could provoke a significant efficacy reduction of existing urban quantity and quality control systems. Copyright © 2011 Royal Meteorological Society

Nosocomial Candidemia in Non-Neutropenic Patients at an Italian Tertiary Care Hospital - R. Luzzati; G. Amalfitano; L. Lazzarini; F. Soldani; S. Bellino; M. Solbiati; M. C. Danzi; S. Vento; G. Todeschini; C. Vivenza; E. Concia (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

A Case of Listeria murray/grayi Bacteremia in a Patient with Advanced Hodgkin's Disease - G. Todeschini; S. Friso; S. Lombardi; M. Casaril; R. Fontana; R. Corrocher (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)